The Effect of Work Discipline and Motivation on Employee Performance at PT. Pos Indonesia Pondokaren Branch - Iman Syatoto (Universitas Negeri Makassar, 2020)
Performance is the work achieved by every employee so that they can make a positive contribution to the company. The purpose of this study was to determine the effect of work discipline and motivation on employee performance at PT. Pos Indonesia Pondok Aren Branch. The method used in this research is descriptive with an associative approach, the sampling technique used is proportional random sampling with a sample of 60 respondents. The analysis tool uses instrument testing, classical assumption testing, regression testing, determination coefficient testing and hypothesis testing. The results of the study concluded that there was a positive and significant effect both partially and simultaneously between work discipline and motivation on employee performance with a contribution of 0.546 or 54.6% while the remaining 45.4% was influenced by other factors. Hypothesis testing obtained F count> F table (34,339> 2,770) thus H0 is rejected and H3 is accepted meaning that there is a positive and significant simultaneous influence between work discipline and motivation on employee performance at PT. Pos Indonesia Pondok Aren Branch.